Դերենիկ Դեմիրճյանի «Գիրք ծաղկանց» պատմվածքը - Լուսինե Վարդանյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье рассказ Дереника Демирчяна “Книга цветов” рассмотрен с двух позиций: с позиции автора и произведения. Герой рассказа - книга и то спасительное значение, которое она имела в жизни армянского народа.Средневековье, которое также является художественным временем рассказа, рассмотрено в качестве средства выражения спасительной роли книги, поскольку этому периоду присущ культ письма и книги. The story “Girg Tsaghkants” (The Book o f Flowers) by Derenik Demirchyan is analyzed in two perspectives - according to the author and the passages about the work. The hero o f the story is the book and the it’s salvific signification, which it has in Armenian’s life. Medieval, which is also artistic time of the story, is viewed as a means of expression to reveal the salvific role of the book, as the worship of writings and books is one of the characteristic features o f Middle Ages.
Keywords: Literature